Peran Ayah Tiri dalam Keharmonisan Anak Tiri dan Pasangannya Persepektif Hukum Islam di Desa Lemper Kecamatan Pademawu Kabupaten Pamekasan - M. Subaidi; Abd. Ghoffar (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the role of stepfathers in maintaining harmony in the families of married stepchildren from an Islamic legal perspective, with the research locus in Lemper Village, Pademawu District, Pamekasan Regency. The background of this study departs from the high phenomenon of stepfamilies in Madurese society and the unclear boundaries of the role of stepfathers after stepchildren establish their own households, which often triggers internal family conflicts. The study uses a descriptive qualitative method with a normative juridical and sociological approach. Primary data were obtained through in-depth interviews with religious leaders, community leaders, and stepfamilies, while secondary data are sourced from fiqh munakahat literature, the Compilation of Islamic Law, and the views of Islamic scholars. Data analysis was carried out interactively through the stages of data reduction, data presentation, and drawing conclusions. The results show that stepfathers do not have a lineage relationship with their stepchildren, so they do not bear the obligation of maintenance, guardianship, or inheritance rights. After the stepchildren marry, the role of the stepfather ideally shifts to that of an advisor with ihsan qualities. Family harmony can be achieved if the stepfather avoids tadakhul fī mā lā ya‘nīhi and limits intervention only to conditions that are truly necessary.